Governing Through Volunteering: The Discursive Field of Government-Initiated Volunteering in the Form of Workfare Volunteering. (April 2019) - De Waele, Els; Hustinx, Lesley
Increasing third-party intervention in volunteering represents a key change in the environment of volunteering. One significant expression is "workfare volunteering": the governmental use of volunteering to foster the economic and/or social reintegration of social assistance recipients. We contribute to existing theory on "third-party volunteering" by studying the shifting discursive field in which volunteering becomes re-entangled with workfare volunteering. Our contribution is based on a governmentality-inspired discourse analysis of internal documents on workfare volunteering in one Belgian social assistance center. We conclude that workfare volunteering entails a strong violation of "voluntary" and "unpaid" properties of volunteering, relegates volunteering to an inferior status relative to paid work, and depicts workfare volunteers as suffering from a clear deficit: the inability to work under regular labor market condition. Through the discursive entanglement of various citizenship frames, the workfare volunteer is cast as an ever-aspiring, yet permanently failing citizen.